PENGARUH STRES DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUMDA AIR MINUM TIRTA MUARE ULAKAN KABUPATEN SAMBAS DALAM PERSPEKTIF BISNIS ISLAM - Wilda; Hutagaluh, Oskar; Oktoviasari, Vera Ayu (Lunggi Journal, 2024)
This study aims to determine the effect of work stress and workload on employee performance at Perumda Air Minum Tirta Muare Ulakan, Sambas Regency, from an Islamic Business perspective. The population of this study consists of all employees of Perumda Sambas, with a sample size of 33 respondents. This research uses a quantitative method and is descriptive statistical in nature. The sampling technique employed is non-probability sampling with saturated sampling or census as the category. The data analysis methods used in this study include validity tests, reliability tests, classical assumption tests, followed by multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination test. The results of this study show that work stress has a positive effect on employee performance at Perumda Air Minum Tirta Muare Ulakan, Sambas Regency, from an Islamic Business perspective, with a multiple linear regression coefficient value of 0.435 and a t-count > t-table value (5.355 > 1.697). Meanwhile, workload also has a positive effect on employee performance at Perumda Air Minum Tirta Muare Ulakan, Sambas Regency, from an Islamic Business perspective, with a multiple linear regression coefficient value of 0.818 and a t-count > t-table value (0.818 > 1.697). Simultaneously, work stress and workload have a positive effect on employee performance at Perumda Air Minum Tirta Muare Ulakan, Sambas Regency, from an Islamic Business perspective, with an F-count > F-table value (63.863 > 3.32).